Effect of electric field on photoionisation cross-section of impurity in multilayered quantum dot - Holovatsky, V.; Chubrey, M.; Voitsekhivska, O. (Superlattices and microstructures, 2020)
The electron - impurity binding energy and photoionization cross-section of hydrogenic impurity are studied in spherical multilayered quantum dot AlxGa1-xAs/GaAs/AlyGa1-yAs driven by external electric field. The problem is solved in the framework of the effective mass approximation and rectangular potential profiles for wells and barriers, using the method of wave function expansion over a complete set of functions obtained as exact solutions of Schrodinger equation in nanostructure without impurity and electric field. The dependence of photoionization cross-section of impurity on electric field intensity is obtained taking into account the excited states of electron. It is shown that the binding energy and photoionization cross-section strongly depend on impurity location, intensity and direction of electric field. If the field is absent, the main contribution into photoionization cross-section is produced by quantum transition of electron from the ground into the first excited state, while if the electric field acts, the main role goes to the transition between ground states of electron with and without impurity. The energy of this transition decreases when electric field intensity increases. •Theoretical model for shallow impurity in core/well/shell QD with finite potential profile is proposed.•The photoionization cross-section of impurity is studied within matrix method.•The peaks of photoionization cross-section, depending on photon energy, are determined by different quantum transitions.•External electric field causes redshift of the lowest peak of photoionization cross-section.•The height of photoionization cross-section lowest peak increases up to its maximum at strong electrical field.